'A STEPPINGSTONE OF CIVILIZATION': THE HOJACK SWING BRIDGE AND THE NEGOTIATION OF SOCIAL POWER IN MONROE COUNTY, WESTERN NEW YORK STATE. (1st November 2012) - Barton, Christopher P; Somerville, Kyle
Abstract : This paper examines the Hojack Swing Bridge, a 1905 railroad swing bridge in western New York State, and its role in the creation of and mediation between structures of power in the region. We first discuss the general design and mechanics of swing bridges, the history of the Hojack railroad in the region, and the effect of the railroad on industrial development in the area. We then demonstrate how the very location and design of the Hojack Swing Bridge was not only the result of geographical considerations, but also the result of competition and compromise between the railroad company and other interests. We close with a brief discussion of the bridge today and its recent demolition as a reflection of this ongoing competition in the present.